CIPPO Evaluation Model for The Madrasah Tahfiz Program “Hubbul Qur’an” at MTs Negeri 6 Model Padang - Danil, Muhammad; Ambiyar, Ambiyar; Aziz, Ishak (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2023)
This paper begins with the existence of the Madrasah Tahfiz Hubbul Qur'an Program at MTs N 6 Padang in 2021 as an improvement to the tahfiz Program which has been implemented in local content learning since 2006. The Program has been implemented for almost a year, so it is necessary to measure and assess the success of the Program. One evaluation model that can be used to measure the implementation of the Madrasah Tahfiz Hubbul Qur'an Program at MTs N 6 Padang is the CIPPO (Contex, Input, Process, Product and Outcome) evaluation model. Through a qualitative descriptive method to provide an overview of the implementation of the Madrasah Tahfiz Hubbul Qur'an Program at MTs N 6 Padang and the results of measurements with the CIIPO evaluation model. After observing, interviewing and documenting, the analysis of the evaluation model of the Madrasah Tahifz Hubbul Qur'an Program at MTs N 6 Padang was carried out by following the work pattern at each stage of the CIPPO model and it was found that the measurement results stated that there was conformity between the implementation and the objectives of the Program, this was due to the existence of 3 factors that influenced the success of the Program, namely 1) The vision and mission factors and the motto of MTs N 6 Padang are in line with the concept and direction of activities in the Program; 2) The availability of human resources, facilities and infrastructure and financing, and; 3) The cooperation factor of parents and students due to the desire to continue to a favourite school through the tahfiz route.